2018
DOI: 10.1016/j.biopsycho.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Will they like me? Neural and behavioral responses to social-evaluative peer feedback in socially and non-socially anxious females

Abstract: The current study examined neural and behavioral responses to social-evaluative feedback processing in social anxiety. Twenty-two non-socially and 17 socially anxious females (mean age = 19.57 years) participated in a Social Judgment Paradigm in which they received peer acceptance/rejection feedback that was either congruent or incongruent with their prior predictions. Results indicated that socially anxious participants believed they would receive less social acceptance feedback than non-socially anxious part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 71 publications
3
7
0
Order By: Relevance
“…We observed a negative memory bias for the overall sample of adolescents. This is in line with the findings from previous studies using the SJP in adult samples which showed that individuals recalled having received significantly more rejection feedback than the actual proportion of rejection provided ( Kortink et al, 2018 ; van der Molen et al, 2018 ). However, our results did not provide support for an increased negative memory bias with higher levels of social anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a negative memory bias for the overall sample of adolescents. This is in line with the findings from previous studies using the SJP in adult samples which showed that individuals recalled having received significantly more rejection feedback than the actual proportion of rejection provided ( Kortink et al, 2018 ; van der Molen et al, 2018 ). However, our results did not provide support for an increased negative memory bias with higher levels of social anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Further, social anxiety and pubertal influences on these feedback predictions and the SPN were examined. The following hypotheses were formulated: (1) We expected to see an overall positive social evaluative feedback expectancy bias ( van der Molen et al, 2014 , 2018 ); (2) Based on literature suggesting that socially anxious individuals expect more negative social evaluation, we predicted that adolescents with higher levels of social anxiety would show a negative social evaluative feedback expectancy bias ( Caouette et al, 2015 ; van der Molen et al, 2014 ); (3) We also expected that high socially anxious adolescents would recall having received fewer acceptance feedback responses, showing a negative memory bias ( Glazier and Alden, 2017 , 2019 ; van der Molen et al, 2018 ); (4) Regarding the SPN, we hypothesized a positive association between SPN amplitudes and social anxiety levels ( Spielberg et al, 2015 ), which would be more pronounced for anticipation of peer acceptance compared with peer rejection ( van der Molen et al, 2014 ). Additionally, we investigated whether the SPN would be larger in older adolescents and adolescents with more advanced pubertal development, since brain development studies have found that self-reported pubertal status may better describe the changes in brain development than age ( Wierenga et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure lasted for a total duration of 2.5 h. Participants filled in a visual analog scale to measure baseline nervousness and approach motivation (see Self-report SPT ratings section) and completed a resting state of 5 min with their eyes closed. Thereafter, participants performed a social judgment paradigm (data presented in Van der Molen, Harrewijn, & Westenberg, 2018 ) and the SPT. After EEG equipment was disconnected, participants filled out self-report questionnaires that were relevant to social anxiety (see Self-reported traits section).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that depression and anxiety may influence neural, cardiac and behavioral responses to social evaluative feedback (Harrewijn et al, 2018;Van Der Molen et al, 2018;Van Der Veen et al, 2016) and the prediction of social feedback (Quarmley et al, 2019;. Furthermore, Fung and Alden (2017) found that Acetaminophen can reduce social anxiety, although half of the reported effect was mediated by a reduction in social pain.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, it might be important and therefore particularly rewarding, for individuals to both be liked and confirmed in their expectations, because it shows that the individual's social theory (i.e., who likes him/her and who does not) is correct (Van Der Veen et al, 2014). This effect, sometimes referred to as the "brain wave of social acceptance", has been replicated in several studies (e.g., Gu et al, 2020;Sun & Yu, 2014;Van Der Molen et al, 2018;Van Der Veen et al, 2016). Lastly, in the SJP, healthy controls seem positively biased regarding their predictions; they expect acceptance about sixty percent of the time (e.g., Gu et al, 2020;Van Der Veen et al, 2016).…”
Section: Introductionmentioning
confidence: 87%